Growth performance of Astyanax altiparanae fed with plant and/or animal lipid sources - Chaves, William; Almeida, Érica C.; Carneiro, Cristiana; Magnone, Larisa; Martins, Nilton; Bessonart, Martin; Zuanon, Jener; Salaro, Ana (Revista de Ciencias Agrícolas, 2019)
The lambari, Astyanax altiparanae, exhibits a great potential for aquaculture due to its omnivory, rapid growth and ease captive production. Despite of fish lipid metabolism being directly related to the dietary lipid consumed, which may lead to changes in fish growth, nothing much have been established regarding the lipid sources that can be applied in A. altiparanae captive production. Thus, this present research was conducted aiming to evaluate the growth performance and whole body composition of A. altiparanae fed with lipid sources of plant and/or animal origins. Were used a Completely Randomized design experiment with five treatments. The treatments consisted of isoproteic and isoenergetic diets, containing the following lipid sources: T1: linseed, chia and sunflower oils; T2: linseed and corn oils; T3: linseed, chia, corn and sunflower oils; T4: sunflower, corn and fish oils; T5: linseed, chia, sunflower, corn oils and bovine fat. Each treatment was replicated six times, where the experimental units consists of 10 fishes (averaged weight: 4.0 + 0.5 g) placed in an aquarium containing 80L of dechlorinated water. Were compared the growth performance parameters among the treatments by applying an one-way analysis of variance (ANOVA) at 5% significance (P < 0.05). The results revealed that both growth performance and whole body composition of A. altiparanae were not affected by the lipid source, which indicate that these fishes can efficiently use both vegetable lipid sources as well as mixtures of vegetable and animal lipid sources without any growth disadvantages.